From governance to government: Banking union, capital markets union and the new EU. (April 2018) - Epstein, Rachel; Rhodes, Martin
European banking union and Capital markets union have emerged as two of the key pillars of European integration since the post-2008 financial crisis. Neither were anticipated prior to the financial crisis, nor was the rapidity of their construction. Both imply the same critical shifts in Europe's institutional political economy. The first relocates national oversight and authority to supranational institutions (a political shift), while the second increases the power and responsibility of market actors by reducing national controls (an economic shift). If banking union aims to break the hold of national governments over banking entities to foster a less fragmented and more efficient European union banking market, capital markets union aims to remove national-level impediments to a single market for capital in which jurisdictional differences are minimized, investor freedoms maximized and business gains access to a greater range of financial resources.